Spanish as an extraordinary source of economic wealth - N. Tsareva (Ибероамериканские тетради, 2019)
The project «The Economic Value of Spanish» proves the importance of Spanish language for the economy of Spain. The most important aspect of its functions is the role that the language plays in the internationalization of Spanish companies; it also multiplies by four commercial exchanges between Spanish-speaking countries. According to the study, Spanish language gives 16% of the economic value of GDP and generates employment for 3.5 million of Spanish citizens. Although Spanish has a lot of prestige in the economic and cultural field, it also lacks certain weaknesses in terms of its importance in the field of Science and Technology.